Faktor-Faktor Yang Berpengaruh Terhadap Perilaku Seksual Remaja - Raudhatul Jannah; Elisa Oktaviani Dewi Anggraeni; Agnes Fridolin (Jurnal Kesehatan Panca Bhakti Lampung, 2025)
Introduction: In the context of teenagers, the term "adolescent sexual behavior" refers to any and all activities that are motivated by sexual desire. Sexually transmitted infections (STIs) like AIDS are one of the consequences of engaging in unsafe sexual conduct. The prevalence of AIDS among those aged 15 to 19 years old in Banjarbaru City is 28.57%, making it one of the cities with the highest infection rate. Through the use of intention, the objective of this research is to investigate the impact that knowledge, attitudes, parenting methods, and spiritual beliefs have on the sexual behavior of adolescents in the city of Banjarbaru. A cross-sectional design was used for the research in this study. Through the use of Cluster Proportional Random Sampling, there were a total of 200 samples. It was a questionnaire that was utilized as the tool. The findings indicated that there was a direct relationship between teenage sexual behavior and knowledge (p = 0.016), parenting approaches (p = 0.004), and spiritual views (p = 0.005). Knowledge, parenting approaches, and spiritual views all have a direct impact on the sexual behavior of adolescents. This direct influence is discussed in the following paragraphs. For this reason, it is strongly suggested that programs be executed with the purpose of enhancing the educational opportunities, parental participation, and spiritual advice available to teenagers. One method that has the potential to be successful in raising adolescents' knowledge of sexual conduct is the development of education programs that are based on the family and religious practices.